Analisis Strategi Pemasaran Terhadap Peningkatan Penjualan Produk Berbasis Digital pada Produk Kecantikan PT Mustika Ratu Tbk - Olivia Elda Ronauli Manurung; Christine Lestari Sitorus (CV. Ulil Albab Corp, 2024)
This study discusses the importance of the role of technology in a company in the field of marketing a product in the digital era, where the role of digital technology will continue to develop along with the changes in the times. This study will explain the marketing strategy of the company PT. Mustika Ratu TBK on beauty products, which are products that have been established since 1975 by Mooryanti Soedibyo, this product has been used by many people for a long time, this is important to know because how the company can utilize sophisticated technology to support their business activities by understanding what business strategies must be updated every day which makes it possible to influence the increase in sales of a company by collecting data from consumers, the company can easily make new innovations for the next product, in addition, with this research will help marketing management in managing their products and what strategies will be used in the company PT Mustika Ratu TBK in increasing product sales in the company and can be introduced to the local and even international community.